Muzambo – palavra brasa dormida: um acidente geo-étnico-econômico soprado na infovia - Magalhães, Luiz Rodolfo (2023)
ABSTRACT The production of the documentary The story with no suit and no tie (2021), about the origins of Muzambinho (a Minas Gerais’ town, in Brazil) made by female teachers of the Public School System, is the discursive event that opens a perspective of archegenealogical analysis, based on Foucauldian Discourse Analysis. It intends to perceive many silences about the quilombola’s origin of the town, presented in historical narratives. Thus, it is studied a book from the period of the New State (Estado Novo), Muzambinho, its history and its people, in order to consider the ruptures that occur between three historical frames (18th, 19th-20th centuries and contemporary/waterway, railroad and infoway/cold, elusive and fertile places), as well as the power relations that operate in this time. It concerns a path through which one can demonstrate how, in each of those frames, certain statements can emerge instead of others in their place, as well as certain regimes of memory can be produced instead of others in their place. In other words, a route departs from the documentary in order to excavate the historical dimension that sustains its irruption: the quilombola’s origin of the town-hygienist erasure of blackness-memory resistance, as a sleeping ember that is lit when the event emerges.